The territorialization of Severe Acute Respiratory Syndrome and its socioeconomic, demographic and public health policy risk factors in Belém, state of Pará, Eastern Amazon, Brazil: a cross-sectional and ecological study. - Nelson Veiga Gonçalves; Alessandra Lima Leal; Heloisa Maria Melo E Silva Guimarães; Arthur Carneiro Bernardes; Silvana Rossy de Brito; Taiana Moita Koury Alves; Tainara Carvalho Garcia Miranda Filgueiras; Thayse Moraes de Moraes; Matheus Pereira do Couto Rocha; Renan Faria Cardoso; Bruno Yudi Shimomaebara Sousa; Claudia do Socorro Carvalho Miranda (PLoS ONE)
Severe Acute Respiratory Syndrome is an important public health problem in Brazil due to the large number of cases. It has a high mortality rate related to risk factors that include systemic arterial hypertension, type 2 diabetes mellitus, male gender and advanced age. This cross-sectional and ecological study analyzed the spatial distribution of this disease related to the evolution of COVID-19 cases and their epidemiological, demographic, socioeconomic and public health policy conditions in the administrative districts of Belém, state of Pará, in the eastern Brazilian Amazon, from 2021 to 2023. Data from the Ministry of Health, the National Institute for Space Research and the Brazilian Institute of Geography and Statistics were used. The statistical and spatial analysis of the data used the chi-square test of equal expected proportions with a significance level of 0.05% and the techniques of ordinary multivariate linear regression and percentiles, with the results expressed by means of choropleth maps, using the Bioestat 5.4 and Arcgis 10.5.1 software. The epidemiological profile analyzed 3,511 cases, following the national pattern with statistical significance. The pathology was not distributed homogeneously in spatial terms and was associated with a territorial and socioeconomic segregation of the population in the neighborhoods and their administrative districts, with great differences in their demographic characteristics, living conditions and public services for treating the disease, especially when we consider the relationship between the outskirts and the center of the municipality. This has revealed unequal development, which has produced health inequalities in the study area. With that in mind, we emphasize the urgency of expanding these services in the places identified as most vulnerable, with a view to equal care access for the disease.